Structure-sensitive transformer and multi-view graph contrastive learning enhanced prediction of drug-related microbes - Xuan, Ping; Wang, Rui; Gu, Jing; Cui, Hui; Zhang, Tiangang (BMC bioinformatics, 2025)
Background: The human microbiome plays a crucial role in regulating the efficacy and toxicity of drugs as well as in developing the drugs. Therefore, predicting the drug-related microbes is beneficial for analyzing the functional mechanisms of drugs. Recently, the graph learning based methods demonstrated their advantages in extracting the node features from the biological heterogeneous graphs. However, the previous methods failed to completely preserve the intrinsic structures of biological data and did not fully utilize the topological and positional information for predicting the drug-microbe associations. Results: We propose a new prediction model, structure-sensitive transformer and multi-view graph contrastive learning for microbe-drug association prediction (SMMDA), to encode and integrate the topological structures, semantics, and multiple-view embedding features of the drugs and microbes. Considering the sparsity of the original features of drugs and microbes, the learnable data augmentation strategy is designed to learn their global representations. Since similar drugs are more likely to associate with the similar microbes, a structure-sensitive transformer is proposed to integrate the topology structures composed of drugs (microbes) to form the multi-view embedding features. We design two contrastive learning strategies to exploit the complementary semantics across multiple views. As the embedding features from multiple views have various semantics, we design view-level attention to adaptively integrate these features. Conclusions: The extensive experimental results show that SMMDA outperforms several state-of-the-art methods for predicting the drug-related candidate microbes. The ablation studies show the effectiveness of the major innovations which include the learnable data augmentation, structure-sensitive transformer-based node feature learning, and multi-view contrastive learning. The case studies on three drugs also demonstrate SMMDA’s capability in retrieving the potential microbe candidates for the drugs.